Half-time evaluation of a new 4-year Ph.D. program in nursing and midwifery at the University of Gondar, Ethiopia - Kerstin Erlandsson; Helena Lindgren; Lena Wettergren; Alemayehu Mekuriaw; Marta Berta; Mengstu Melkamu; Tewodros Seyoum; Solomon Hailemeskel; Abebaw Jember; Mohammed Hassen; Mignote Gebrie; Biftu Geda; et al. (Global Health Action)
A new four-year Ph.D. programme in nursing and midwifery, the first of its kind in Ethiopia, was started in 2018/2019 at the University of Gondar when eight doctoral students in nursing and midwifery entered the program. We who have been involved see this as an appropriate time to evaluate what has been accomplished to date and to look toward future possibilities. Our aim in carrying out such an evaluation and presenting our findings is in part to determine if similar programs might be developed in other similar settings and in part to learn what modifications to the present program might be considered. The key elements of a questionnaire survey with closed and open response alternatives were based on the content, structure and learning outcomes of the home university Ph.D. programme as described in the curriculum. The questionnaire responses captured changes that would be needed to maintain a fully satisfactory programme that blends onsite instruction and online access to faculty resulting in a twenty-first century blended Ph.D. programme. Improved dialogue between the home university faculty and the external supervisors is needed. The programme can provide a career pathway that midwifery and nursing educators can follow in their own country rather than having to leave to study in another country. The findings provide insight into the feasibility of extending similar Ph.D. programmes to other parts of East Africa and with the SDG 5 in mind with an increased focus on women leadership. The justification for this initiative is to meet the need for more nursing and midwifery faculty who can provide quality midwifery and nursing education in East African countries. Retention of these professionals will help to deal with the shortage of healthcare personnel and will provide better care for the general population.